Religiusitas Dan Literasi Terhadap Kecenderungan Pembayaran Zakat Digital Pada Kalangan Pekerja Milenial Daerah Gresik Utara - Muhammad Yusuf Aria Widjaja; Dina Anisya Rufaedah; Suci Reza Syafira (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
Millennials are skilled in digital transactions and are considered capable of understanding giving zakat. This research has differences from previous research by using the discussion of millennial generation subjects. The tradition of gotong-royong and religiosity factors have an impact on the high level of generosity of Indonesian society. The millennial generation can apply this tradition in the pattern of digitalisation of zakat to increase efficiency and transparency. Gresik Regency has many jobs and companies, making it a labour-intensive district with a diversity of labour force participation. This quantitative research uses a questionnaire processed by the SPSS programme where sampling is accidental sampling of 99 respondents. The data analysis used is multiple regression analysis, classical assumption tests of normality, heteroscedasticity, and multicollinearity and partial and simultaneous hypothesis testing. The results showed that the variables of religiosity (X1) and literacy (X2) simultaneously and partially had an influence on the tendency to pay digital zakat among millennial workers in the north Gresik area. The recommendation in this study is that further researchers add other variables in influencing the level of digital zakat payment. Meanwhile, zakat institutions can continue to increase transparency and invite people to increase their religiosity in order to gain more trust from millennial muzakki.